1998
DOI: 10.1007/bf02460905
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis and predicted secondary structures of the rDNA internal transcribed spacers of the powdery mildew fungi (Erysiphaceae)

Abstract: The nucleotide sequences of the internal transcribed spacer (ITS) regions of the ribosomal DNA including the 5.8S rRNA gene and the 5' end of the 28S rRNA gene have been determined for 19 species in 10 genera of the powdery mildew fungi in order to analyze their phylogenetic relationship. These fungi were divided into two large groups based on the nucleotide length of the ITS regions, and this grouping was in line with that based on the morphological characters of the anamorphic stage rather than the teleomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
1
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 30 publications
1
44
1
2
Order By: Relevance
“…The present analysis as well as our previous report (Takamatsu et al, 1998) clearly showed the close relationship between Erysiphe (section Erysiphe) and Microsphaera, but did not support the traditional evolutionary hypothesis (Blumer, 1933;Braun, 1987) Fig. 2 by the log-likelihood ratio test (Kishino and Hasegawa, 1989).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The present analysis as well as our previous report (Takamatsu et al, 1998) clearly showed the close relationship between Erysiphe (section Erysiphe) and Microsphaera, but did not support the traditional evolutionary hypothesis (Blumer, 1933;Braun, 1987) Fig. 2 by the log-likelihood ratio test (Kishino and Hasegawa, 1989).…”
Section: Discussioncontrasting
confidence: 49%
“…We excluded Erysiphe section Golovinomyces from the current analysis because the section was revealed to be distantly related to both Microsphaera and Erysiphe section Erysiphe in our previous study (Takamatsu et al, 1998).…”
mentioning
confidence: 99%
“…Blumeria graminis is regarded as an isolated fungus among the Erysiphales, because of its unique morphological charactristics and also its unique parasitism to monocots, especially cereal plants, in contrast to the dicot parasitism of most other Erysiphales. Recent molecular works have supported the isolated phylogenetic placement of B. graminis (Takamatsu et al, 1998;Saenz and Taylor, 1999;Mori et al, 2000). The nucleotide sequence data from other species of the Erysiphales are required to clarify the phylogenetic relationship of the Erysiphales among Ascomycota more precisely.…”
mentioning
confidence: 98%
“…(Cook et al 1997). According to Takamatsu et al (1998Takamatsu et al ( , 1999) Erysiphe s. str. and Microsphaera do not group into separate monophyletic lineages, but form several small mixed clusters, which cannot be phylogenetically distinguished from each other.…”
Section: Discussionmentioning
confidence: 99%